2006
DOI: 10.1142/s0192415x06003989
|View full text |Cite
|
Sign up to set email alerts
|

The Study of Dynamic Response to Acute Hemorrhage by Pulse Spectrum Analysis

Abstract: Traditional Chinese Medicine (TCM) holds that blood and qi are fundamental substances in the human body for sustaining normal vital activity. The theory of qi, blood and zang-fu contribute the most important theoretical basis of human physiology in TCM. An animal model using conscious rats was employed in this study to further comprehend how organisms survive during acute hemorrhage by maintaining the functionalities of qi and blood through dynamically regulating visceral physiological conditions. Pulse waves … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Furthermore, the cardiovascular system is an electrically driven mechanical-pumping system, and the organ resonance theory is verified via the accordance of the spectral distribution of the electrocardiogram (ECG) as well as the arterial pulse [16, 17]. Furthermore, the specifically different patterns of the harmonic components of the arterial pulse among surviving and expired rats that suffered from acute bleeding and progressive hemorrhaging were studied [18, 19]. However, the previously mentioned spectral-domain studies focus on the frequency range of 0–10 Hz, where most arterial pulse energy is concentrated.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the cardiovascular system is an electrically driven mechanical-pumping system, and the organ resonance theory is verified via the accordance of the spectral distribution of the electrocardiogram (ECG) as well as the arterial pulse [16, 17]. Furthermore, the specifically different patterns of the harmonic components of the arterial pulse among surviving and expired rats that suffered from acute bleeding and progressive hemorrhaging were studied [18, 19]. However, the previously mentioned spectral-domain studies focus on the frequency range of 0–10 Hz, where most arterial pulse energy is concentrated.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported from previous work that all harmonics are shifting towards a new equilibrium in rats during the recovery stage of acute hemorrhage. It has also been demonstrated that the 2nd and 3rd harmonics which are related to the Kidney and Spleen respectively, showed significant increases (Chang et al, 2006). When these regulating mechanisms fail to function or external damage is persistent, the entire system will disintegrate and it will possibly cause death.…”
Section: Introductionmentioning
confidence: 99%